Toxins in broilers, infectious diseases in cats, and environmental conditions for welfare of pigs - Carvalho, Leonardo Bianco (Revista de Ciências Agroveterinárias, 2023)
In a current research, OLIVEIRA et al. (2018) presented a review article on the importance of mycotoxins in poultry production, especially for broilers. They evidenced some mycotoxins are harmful to human and animal health and may be an obstacle to the poultry economy due to food contamination. The most observed effects are generally the immunosuppression, hepatotoxicity and nephrotoxicity, such as decreased performance and production gains. For contamination control, it is required the adoption of suitable agricultural practices to prevent the growth of fungi, by using biological, physical and/or chemical decontamination methods, although the physical process with adsorbents mixed with the feed is more widely used. Due to the importance of mycotoxins for poultry production, it is also necessary to adopt measures to avoid contamination, besides developing a program of control and production of toxins and antifungal growth. BIEZUS et al. (2018) investigated the occurrence of infectious diseases in cats to identify the main clinical signs presented for each of them. Authors found 75% of viral infectious diseases, 12.5% of bacterial infectious diseases, 9.4% of fungal infectious diseases, 3.1% of protozoan infectious diseases. Among the most frequent infectious diseases were feline leukemia virus (39.4%) and clinical manifestations were found to be anemia (50,00%), leukemia (33.3%) and lymphoma (16.7). Authors concluded that unvaccinated male cats with free access to the street and direct contact with other felines were more numerous among the patients, which shows the close relationship of the lack of basic health care of these animals with the occurrence of the infectious diseases in the species. SANTOS et al. (2018) stated environmental modifiers, such as the use of water depths, are often used to produce pigs in order to improve welfare conditions and consequently production. So, they studied the effect of the environment on the weight gain and the behavior of pigs with and without access to the water. In general, they found the highest demand for water occurred during the afternoon due to the higher temperature in relation to the morning. In addition, the animals showed lower average daily weight gain at higher temperatures. Finally, authors concluded the water supply does not influence on the animals' weight gain, however it provides better welfare conditions.